Microbial Diversity and Metabolite Profile of Fermenting Millet in the Production of Hausa koko, a Ghanaian Fermented Cereal Porridge - Atter, Amy; Diaz, Maria; Tano-Debrah, Kwaku; Kunadu, Angela Parry-Hanson; Mayer, Melinda J.; Colquhoun, Ian J.; Nielsen, Dennis Sandris; Baker, David; Narbad, Arjan; Amoa-Awua, Wisdom (Frontiers in Microbiology, 2021)
Hausa koko is an indigenous porridge processed from millet in Ghana. The process involves fermentation stages, giving the characteristic organoleptic properties of the product which is produced largely at small-scale household level and sold as a street food. Like many other indigenous foods, quality control is problematic and depends on the skills of the processor. In order to improve the quality of the product and standardize the process for large-scale production, we need a deeper understanding of the microbial processes. The aim of this study is to investigate the microbial community involved in the production of this traditional millet porridge and the metabolites produced during processing. High throughput amplicon sequencing was used to identify the bacterial (16S rRNA V4 hypervariable region) and fungal (Intergenic Transcribed Spacer (ITS)) communities associated with the fermentation, whilst Nuclear Magnetic Resonance (NMR) was used for metabolite profiling. The bacterial community diversity was reduced during the fermentation processes with an increase and predominance of lactobacilli. Other dominant bacteria in the fermentation included Pediococcus, Weissella, Lactococcus, Streptococcus, Leuconostoc and Acetobacter. The species Limosilactobacillus fermentum and Ligilactobacillus salivarius accounted for some of the diversities within and between fermentation time points and processes. The fungal community was dominated by the genus Saccharomyces. Other genera such as Pichia, Candida, Kluyveromyces, Nakaseomyces, Torulaspora, Cyberlindnera were also classified. The species Saccharomyces cerevisiae, Stachybotrys sansevieriae, Malassezia restricta, Cyberlindnera fabianii and Kluyveromyces marxianus accounted for some of the diversities within some fermentation time points. The species Stachybotrys sansevieriae and Malassezia restricta may have been reported for the first time in cereal fermentation. This is the most diverse microbial community reported in Hausa koko. In this study we could identify and quantify thirty three key different metabolites produced by the interactions of the microbial communities with the millet, comprised of organic compounds, sugars, amino acids and intermediary compounds and other key fermentation compounds. An increase in the concentration of organic acids in parallel with the reduction of sugars occurred during the fermentation process while an initial increase of amino acids followed by a decrease in later fermentation steps was observed.